Cost of air pollution by particulate matter generated by vehicular transport in Metropolitan Lima - Silva Vivanco, Cindy (2021)
High concentrations of particulate matter (PM) represent a risk to human health, one of its greatest sources is the existing vehicle fleet in Metropolitan Lima City (ML). Due to this problem, various regulatory measures have been established to mitigate this high level of contamination. This article aims to estimate the economic cost of air pollution by particulate matter generated by vehicular transport in Metropolitan Lima. This is the starting point for the design and implementation of policy measures in an efficiency context. For this purpose, the factors of the concentration-response function were used in order to estimate the number of cases of mortality and morbidity associated with the concentration of PM. The results show that the cost fluctuated between 0.21% and 0.29% of the Gross Domestic Product (GDP) of LM, a significantly lower fraction in relation to other densely populated cities. No cost trend was identified, which would seem to be more linked to atmospheric and geographic dynamics than to other factors such as population growth, increase in the vehicle fleet, or regulatory measures for vehicle transport.